Literature Review: Role of Neurosurgery in Leptomeningeal Carcinomatosis - Ogasawara, Thaís Mitie; Batista, Thaís Yumi Kobayashi; dos Santos, Rafael Rodrigues Pinheiro; Rampazzo, Ana Carla Mondek; Badaoui, Caroline Amane Pessoa; Caetano, Igor Ruan de Araújo; Martins, Jonathan Vinícius; Nogueira, Maria Letícia; Guarnieri, José Ângelo; Zicarelli, Carlos Alexandre Martins (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Introduction Leptomeningeal carcinomatosis results from metastatic neoplastic cells that reach the leptomeninges through the cerebrospinal fluid. The presentation of the disease is variable, making prognosis challenging. However, the presence of intracranial hypertension is common, which has prompted new treatments to mitigate this effect.Objective To report the role of neurosurgery in the treatment of leptomeningeal carcinomatosis, as well as its advances.Methodology Literature review with a search of the PubMed database, between 2011 and 2021, using the following descriptors: Neurosurgery, Leptomeningeal Carcinomatosis, Cerebrospinal and Treatment. A total of 42 articles were found, 16 of which were selected.Results The shunt insertion considerably improved the effects of cranial hypertension, increasing the average survival time of patients by 3.5 months after surgery. The Ommaya reservoir is also a viable option due to its convenience and safety. The V-Port, on the other hand, has overcome the challenges of conventional devices, with shorter operating times (42 minutes), smaller skin incisions, and no reports of postoperative infection.Conclusion Devices for the treatment of leptomeningeal carcinomatosis have been steadily improving, simplifying surgical procedures and benefiting patients.
Keywords: neurosurgery; leptomeningeal carcinomatosis; cerebrospinal; treatment